Perancangan Sistem Informasi Promosi dan Penjualan Berbasis Web Pada Unit Produksi SMKN 1 Ampek Angkek Menggunakan Framework CodeIgniter - Nurul Abdillah; Oki Dahwanu; Hamzah Alghifari; Niko Akbar (Jurnal Informatika, 2024)
The Production Unit (PU) plays an important role in fostering students’ entrepreneurial skills through the creation of economically valuable products and services. However, product promotion at the Production Unit of SMK N 1 Ampek Angkek has so far only been carried out through exhibitions held once every semester. The school’s less strategic location results in many products remaining unsold, and those stored for too long often become damaged. To address this issue, a web-based promotional and sales information system was designed using the CodeIgniter framework. The system was developed using UML (Unified Modeling Language) modeling with an object-oriented approach. The programming languages used were PHP with the CodeIgniter framework and JavaScript, while MySQL served as the database and Sublime Text 3 as the code editor. The result of this design is a web-based information system that can present craft product information more widely and efficiently. This system helps the Production Unit promote its products without time and location limitations and provides convenience for consumers to view and purchase products online.